The Nador dipole: one of the main magnetic anomalies of the NE Rif - Anahnah, F.; Galindo-Zaldívar, J.; Azzouz, O.; Ruano, P.; Chalouan, A.; Pedrera, A.; Ruiz-Constan, A.; Bouregba, N. (TRABAJOS DE GEOLOGÍA, 2009)
The most intense total field magnetic anomaly of the northeastern Rif is an E-W elongated dipole, with more than 320 nT amplitude, centred in Nador and extending from Oued Kert up to Cap de l’eau (96×70 km). This anomaly is related to the Neogene-Quaternary intermediate and basic volcanic rocks, like the Gourougou volcano. The new measured field magnetic anomalies and susceptibilities allow us to study this dipole for the first time, to constrain the shape, distribution, structure and deep extension of the volcanic rocks. This study improves the knowledge of crustal structures related to the southern boundary of the Alboran Sea.